2017
DOI: 10.3389/fncel.2017.00226
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Mechanisms Mediating the Pro-Nociceptive Action of Hydrogen Sulfide in Rat Trigeminal Neurons and Meningeal Afferents

Abstract: Hydrogen sulfide (H2S), a well-established member of the gasotransmitter family, is involved in a variety of physiological functions, including pro-nociceptive action in the sensory system. Although several reports have shown that H2S activates sensory neurons, the molecular targets of H2S action in trigeminal (TG) nociception, implicated in migraine, remains controversial. In this study, using suction electrode recordings, we investigate the effect of the H2S donor, sodium hydrosulfide (NaHS), on nociceptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 52 publications
2
24
0
1
Order By: Relevance
“…As we (Koroleva et al, 2017 ) and others (Roa-Coria et al, 2019 ) showed that the action of H 2 S is mediated, at least, partly by TRPV1 receptors, it could be that this inhibition is due the negative crosstalk between TRPV1 and P2X3 receptors. Thus, it has been shown previously in isolated neurons that the activation of TRPV1 receptors decreased the subsequent activation of ATP-gated P2X3 receptors (Stanchev et al, 2009 ).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…As we (Koroleva et al, 2017 ) and others (Roa-Coria et al, 2019 ) showed that the action of H 2 S is mediated, at least, partly by TRPV1 receptors, it could be that this inhibition is due the negative crosstalk between TRPV1 and P2X3 receptors. Thus, it has been shown previously in isolated neurons that the activation of TRPV1 receptors decreased the subsequent activation of ATP-gated P2X3 receptors (Stanchev et al, 2009 ).…”
Section: Resultsmentioning
confidence: 71%
“…The main finding of this study is that in meninges, the gaseous transmitter H 2 S exerts the multicomponent protecting action against the powerful nociceptive agent, extracellular ATP. This finding is unusual as H 2 S can itself transiently promote nociceptive firing in trigeminal afferents (Koroleva et al, 2017 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A relatively recent publication detected activation of TRPV1 channels in rat TRG neurons by NaHS based on inhibition by capsazepine. However, the majority of investigators in the sulfide field consider the gasotransmitter as selective for TRPA1 channels and evidence for activation of TRPV1 channels is scarce (Trevisani et al ., ; Ang et al ., ; Medeiros et al ., ; Lu et al ., ; Koroleva et al ., ; Yu et al ., ). No individual excitatory action but potentiation of the capsaicin‐induced response by NaHS was reported in isolated vagal neurons from rat lungs .…”
Section: Effects Of Sulfur Species Mediated By Trpa1 Channelsmentioning
confidence: 97%
“…Hydrogen sulfide (H 2 S) and NO, members of the gasotransmitter family, are involved in the regulation of a great variety of physiological functions, including cardiovascular functions, nociception and inflammation [149,150]. A substantial body of evidence indicates that H 2 S increases the firing rate of trigeminal ganglion neurons by acting on TRP receptors [56,151]. H 2 S is synthesized from cysteine through several enzymatic pathways.…”
Section: Sensitization Processes Within the Trigeminovascular Systemmentioning
confidence: 99%